Reinach and the Foundations of Private Law (Cambridge University Press, 2026)
This volume highlights essays by legal scholars and philosophers on the legal philosophy of Adolf Reinach. Though Reinach has been the subject of resurgent recent interest in private law theory, his work remains oblique to many contemporary legal theorists and students. This volume situates his contributions in contemporary theory.